Материалы к фауне и систематике гельминтов рода Triodontophorus (Nematoda, Strongylidae) - Двойнос, Г.М.; Харченко, В.А. (Вестник зоологии, 1985)
Four Triodontophorus species are found in horses of different areas of the Soviet Union. T. nipponicus, a species new for the USSR fauna, is redescribed; Equus hemionus and E. przewaskii are for the first time established as hosts. T. popowi is sunk in synonymy of T. tenuicollis.